Nanoparticle assisted gemini surfactant as wax deposition suppressant in Malaysian crude oil using experimental and molecular dynamics simulation - Shamala Devi, Vijaya Kumar (2022)
Wax deposition can cause a slowdown or halt in operation by restricting crude oil flow in the pipeline due to the wax blockage and triggering pressure irregularities. Chemical inhibitors interact with the wax molecule in crude oil and prevent large wax molecules from attach. The use of Gemini surfactant and nanoparticles to prevent wax deposition is still in its infancy. In this thesis, the efficiency of Gemini surfactant 2,5,8,11 Tetramethyl 6 dodecyn-5,8 Diol Ethoxylate (GS), three different nanoparticles: silicon dioxide (NP1), tin oxide (NP2) and nickel (III) oxide (NP3) and their blends at different operating conditions are assessed to study their influence on the crude oil viscosity using Brookfield DV-III viscometer and wax inhibition using cold finger analysis. In addition, molecular dynamics modeling (MD) is used to analyze the intermolecular interaction between a wax molecule (n-icosane) with inhibitors using Accelrys Material Studio 8. The interaction of wax molecules with inhibitors were analysed through radial distribution function (rdf) value. The separate use of GS and nanoparticles significantly reduced crude oil viscosity and wax deposition. However, combining the GS and nanoparticles showed better performance than their corresponding individual use in viscosity and cold finger analysis. Overall, the viscosity of crude oil was reduced by about 85-92% at 10℃ with the addition of GS and nanoparticles. The highest viscosity reduction obtained was 92.8% using the blend of GS and NP1. The addition of nanoparticles to GS improved their inhibition efficiency by providing dispersion. Nevertheless, the use of GS and nanoparticles individually achieved a paraffin inhibition efficiency (PIE) of 45-48%. The highest PIE of 61.6% was achieved by GS/NP3 blend while the lowest was 45.3% with NP1 individual used. For the MD results, GS/NP3 blend shows the weakest wax-wax intermolecular interaction with n-icosane, indicating higher wax solubility with the highest radial distribution function (rdf) value of 5.25 Å. Also, the GS/NP3 blend has the stronger van der Waals (vdW) interaction with a hydrogen atom in n-icosane compared to the individual systems of GS and NP3 separately. This can be due to the presence of the O carbonyl group in both GS and NP3, which can establish a higher number of bonds. Therefore, wax inhibition in n-icosane is higher in GS/NP3 blend compared to the individual system of GS and NP3. An experimental study through cold finger analysis validated simulation result which proved that the GS/NP3 blend significantly reduced the wax formation by 61.6%. In comparison, the individuals of GS and NP3 reduced wax formation by 46.5% and 47.7% respectively. Overall, the combination of GS and NP3 has shown highest efficiency in wax inhibition through cold finger analysis and highest wax solubility in rdf analysis. Thus, GS/NP3 blend is the best inhibitor among tested inhibitor combinations in inhibiting wax in Malaysian crude oil.